2022
DOI: 10.3390/buildings12060808
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Appropriate Reverberation Time for Lower-Grade Elementary School Classrooms Using Speech Intelligibility Tests

Abstract: Because speech recognition performance is significantly lower at the age of nine or younger, the acoustic performance standards of classrooms for young children should be investigated. This study derives the appropriate reverberation time for lower-grade elementary school classrooms in Korea. A virtual sound field was created by computer modeling using normalized classrooms of Korean elementary schools. A total of five classrooms with reverberation times from 0.6 s to 1.2 s were produced by varying the sound a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Elementary classrooms in Korea should have an RT of <0.6 s [2]. Table 6 shows the configurations that produced RTs of ≤0.6 s. The 1/10-scale model yielded a shorter RT than the other experimental methods.…”
Section: Reverberation Timementioning
confidence: 99%
See 2 more Smart Citations
“…Elementary classrooms in Korea should have an RT of <0.6 s [2]. Table 6 shows the configurations that produced RTs of ≤0.6 s. The 1/10-scale model yielded a shorter RT than the other experimental methods.…”
Section: Reverberation Timementioning
confidence: 99%
“…The hearing abilities of lower elementary students must be considered when designing classrooms to facilitate their education. The following acoustic standards for lower elementary students have been proposed in Korea to ensure speech intelligibility [2,3]: a reverberation time (RT) of <0.6 s (unoccupied) and background noise level of <35 A-weighted decibels (dB(A)) for a classroom volume of <185 m 3 . Ensuring that the acoustic environment of lower elementary classrooms meets these standards will help to improve the learning efficiency of students.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Listening in an environment with poor acoustics necessitates greater concentration [11] which could lead to a decrease in students learning achievement [8]. Thus, students learning development is greatly influenced by the classroom acoustic quality [12]. On the other hand, the acoustics of the classroom have a substantial impact on the teacher's well-being.…”
Section: Overview Of Classroom Acousticmentioning
confidence: 99%
“…All the surfaces mentioned above have low absorption coefficients, thus more sound energy is reflected within the lecture rooms. A study by Jo et al (2022) found that classrooms wall equipped with soundabsorbing boards demonstrate optimal reverberation time (RT) conditions in comparison to classrooms with painted cement surface. Furthermore, classes that utilize carpet flooring attained the recommended RT value of 0.6 seconds, in contrast to classrooms equipped with marble flooring (Ahmad, 2020).…”
Section: Reverberation Time (T30)mentioning
confidence: 99%